Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fnmol.2017.00283
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Sequencing Analysis Reveals a Regulatory Role for Transcription Factor Fezf2 in the Mature Motor Cortex

Abstract: Forebrain embryonic zinc finger (Fezf2) encodes a transcription factor essential for the specification of layer 5 projection neurons (PNs) in the developing cerebral cortex. As with many developmental transcription factors, Fezf2 continues to be expressed into adulthood, suggesting it remains crucial to the maintenance of neuronal phenotypes. Despite the continued expression, a function has yet to be explored for Fezf2 in the PNs of the developed cortex. Here, we investigated the role of Fezf2 in mature neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
2
6
0
1
Order By: Relevance
“…In neurons, both FEZF2 and IKZF1 are important TFs that determine neuroprogenitor cell fate 70 . FEZF2 also promotes neuroplasticity and neuronal signaling that involves neuroactive ligand-receptor interaction, cell adhesion molecules, and calcium signaling pathways 71 , thereby strikingly paralleling our KEGG 56 pathways enrichment findings here (Fig. 2 and Supplementary Tables S4 – S6 and S10 ).…”
Section: Discussionsupporting
confidence: 82%
“…In neurons, both FEZF2 and IKZF1 are important TFs that determine neuroprogenitor cell fate 70 . FEZF2 also promotes neuroplasticity and neuronal signaling that involves neuroactive ligand-receptor interaction, cell adhesion molecules, and calcium signaling pathways 71 , thereby strikingly paralleling our KEGG 56 pathways enrichment findings here (Fig. 2 and Supplementary Tables S4 – S6 and S10 ).…”
Section: Discussionsupporting
confidence: 82%
“…We initiated this study with the aim of identifying genetic targets of FEZF2, a transcription factor necessary for the proper specification of CSNs and CST formation. FEZF2 activates and represses gene expression in the cerebral cortex (Clare et al, 2017;Lodato et al, 2014), including in CSNs in L5. Here, we found that FEZF2 activates the expression of Rnd3, which is cell autonomously required for the proper regulation of axon elongation, dendritic complexity, and spine formation in CSNs.…”
Section: Discussionmentioning
confidence: 99%
“…The R package pvclust, which calculates an approximately unbiased (AU) and bootstrap (BP) p -value for each cluster, was used to cluster the highly variable genes (Suzuki and Shimodaira, 2006 ). Heatmap generation was performed as described in Clare et al ( 2017 ).…”
Section: Methodsmentioning
confidence: 99%